(untitled) (Eurasian Medical Research Periodical, 2023)
During the COVID-19 pandemic, the relevance of the dynamics of the prevalence of cardiovascular diseases (CVD) increases. The purpose of the study. To evaluate the associative links between the frequency of detection of a new coronavirus infection and the prevalence of CVD, taking into account cardiovascular comorbidity, the severity of COVID-19 and postcovid syndrome (PKS). Against the background of cardiac comorbidity, every fifth participant in the study had an asymptomatic and every second had a symptomatic form of COVID-19. The frequency of detection of COVID-19 does not depend on gender, age, presence or absence of cardiovascular diseases. The frequency of detection of cardiovascular diseases naturally increases with increasing severity of COVID-19. Postcovid syndrome was registered in 41.4% of COVID-19 survivors, it developed more often in women, increased with age, the severity of the disease and depended on the presence or absence of cardiovascular diseases. The course of COVID19 and the development of postcovid syndrome were negatively affected by tobacco smoking and alcohol abuse.